Between Satisfaction and Suspicion: Minority Shareholders' Lived Experiences of Dividend Policy in Concentrated Ownership Firms - Dewa Putu Yohanes Agata L. Sandopart (CV. Global Cendekia Inti, 2024)
This study aims to explore the lived experiences of minority shareholders regarding dividend policy in companies with concentrated ownership. Departing from previous studies dominated by quantitative-positivistic approaches, this research employs interpretative phenomenological analysis to capture the subjective meanings behind dividend policy outcomes. Through in-depth interviews with six minority shareholders in Indonesian public companies, this study identifies four superordinate themes, including the ambivalence of dividend reception, where high dividends raise concerns of long-term expropriation while low dividends trigger suspicions of tunneling, organized resignation as a dominant coping strategy through exit and the development of information networks, limited voice reflected in the perception of the General Meeting of Shareholders as a formal ritual without substantive impact, and a universal trust deficit in which suspicions of expropriation are shared across participants. This study contributes to the corporate governance literature by presenting an emic perspective that has been largely overlooked and by extending the application of interpretative phenomenological analysis into the field of finance and corporate governance.